2006
DOI: 10.1177/0363546505284186
|View full text |Cite
|
Sign up to set email alerts
|

Weakness in End-Range Plantar Flexion after Achilles Tendon Repair

Abstract: Impairments will have functional implications for activities (eg, descending stairs and landing from a jump). Weakness in end-range plantar flexion may be an unrecognized problem after Achilles tendon repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
150
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(156 citation statements)
references
References 20 publications
5
150
1
Order By: Relevance
“…For example, the maximal ankle plantar flexion joint moment while walking occurs at a joint position of 15-20° dorsiflexion (Winter, 1984). At this ankle joint angle, the passive joint moment can achieve values between 20 and 30·Nm (Riener and Edrich, 1999;Mullaney et al, 2006). Moreover, due to the viscoelastic behaviour of the connective tissues, in a dorsiflexed position the passive ankle joint moments may be higher in a dynamic condition (Gajdosik et al, 2005) such as walking.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the maximal ankle plantar flexion joint moment while walking occurs at a joint position of 15-20° dorsiflexion (Winter, 1984). At this ankle joint angle, the passive joint moment can achieve values between 20 and 30·Nm (Riener and Edrich, 1999;Mullaney et al, 2006). Moreover, due to the viscoelastic behaviour of the connective tissues, in a dorsiflexed position the passive ankle joint moments may be higher in a dynamic condition (Gajdosik et al, 2005) such as walking.…”
Section: Discussionmentioning
confidence: 99%
“…The deficits related to strength, heel-rise height, range of motion, and increase in tendon length are comparable to those found in other patients with an Achilles tendon rupture. 15,23,31 These deficits are seen in both surgically and nonsurgically treated patients. 20,24,35 This patient's self-reported outcome (Achilles tendon Total Rupture Score, 83/100) indicated some limitation/difficulty with various activities, which was similar to that reported by patients 1 year after injury in other studies.…”
Section: Tablementioning
confidence: 99%
“…2,14,16,18 However, the majority of these patients have residual weakness and decreased function 1 year after treatment. 4,15,23,31 This may be due, in part, to the fact that the tendon often heals in an elongated position after a rupture. 11,22 Tendon elongation and weakness result in gait asymmetries such as increased ankle dorsiflexion and decreased plantar flexion moment of the involved limb.…”
mentioning
confidence: 99%
“…Kangas et al 10 report better outcome with less elongation after surgical treatment. However, Mullaney et al 19 reported end-range plantar flexion weakness in a surgically treated group.…”
mentioning
confidence: 96%
“…4 Tendon injuries heal slowly, and the normal structure and mechanical properties are often not recovered fully. 16,19,23 Residual weakness and impaired function following ATR may interfere with muscle work and physical activities. 2,20,23 Olsson et al 23 found that calf muscle strength remained reduced by 10% to 30% after 2 years with both surgical and nonsurgical treatment, which can be explained in part by elongation of the tendon.…”
mentioning
confidence: 99%